PENGARUH LABA/RUGI, OPINI AUDIT, DAN KOMPLEKSITAS OPERASI PERUSAHAAN TERHADAP AUDIT DELAY - Putra, Hilman Nabil Syah; Musyaffi, Ayatulloh Michael; Sasmi, Aji Ahmadi (LPPM Universitas Bina Bangsa, 2023)
The purpose of this study was to determine how the effect of the effect of profit/loss , audit opinion and complexity company operations against audit delay (Study Empirical on Mining Companies Listed on the Indonesia Stock Exchange 2020-2022). The population in this study are mining sector companies that are consistently listed on the IDX in 2020-2022, for total of 50 companies. The sampling method in this study used a purposive sampling method. The type of research used in this study is quantitative research using Logistic Regression Analysis and processed using the IBM SPSS Version 26 program. The results of this study state that: Variabel Profit/Loss (LR) has a negative effect on Audit Delay (AD); (2) Variabel Audit Opinion (OA) did not affect the Audit Delay (AD); (3) Variabel Complexity Company Operations (KOP) did not affect the Audit Delay (AD).